Consum’actors : who are they and what drives them to boycott and buycott? - Jacquet, Julie (2021)
With the rise of consumer’s consideration for sustainability issues and the increased accessibility and prevalence of digital tools, consumers have more opportunities than ever to voice their concerns. This study will focus on the users of a web platform for boycott campaigns, called i-boycott.org, and a mobile application that supports boycott and buycott, called BuyOrNot. Both of those digital tools were developed by the French organization I-buycott, whose followers and users of its tools are called “consum’actors” because they are empowered consumers, actors of their own consumption. Firstly, to know more about the consum’actors, this study investigated what the profile of I-buycott’s tools users is by examining their socio-demographic characteristics, their value orientation, and their perceived marketplace influence. Secondly, this study explored which factors influence their participation in online boycott campaigns on the i-boy- cott.org platform. To that end, a quantitative study was conducted based on the data from a survey shared with the followers of I-buycott on social media. The results of this study showed that consum’actors are mostly younger female adults who have a fairly high level of education and earn an average to decent income. What drives them the most to participate in boycotts is their biospheric value and their concern for the natural environment.